THE DUTCH COLONIAL ECONOMIC’S POLICY ON NATIVES LAND PROPERTY OF INDONESIA - Chairul Fahmi (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2020)
This paper analyzes the historical shifts of land property rights in Indonesia's archipelago and how new land laws were formed, especially during the Dutch colonization era. After the Netherlands East Indies (NEI) established in the 18th century and proclaimed itself as a sovereign landlord over the East Indies (Indonesia), the role of indigenous law (adat law) and its rights to lands have diminished by a new form of law namely the European law system (the civil code). By adopting the European civil code, the colonial Dutch declared all uncertified lands and all forests’ resources were the Dutch colonial State's property and to be managed by the colonial authority [State’s domain]. For Adat peoples, these rights belong to them, either as individuals or as groups, and it had been recognized by their customary law (adat law) legally, which they have had since their ancestors inhabited within the land, territories, and resources. Further significant impact toward the adat rights to land, when the Agrarian Act (agrarisch wet) applied in 1870 by the colonial government, had severely impacted towards the land right of indigenous peoples in Indonesia, by which most of them had lost their adat property right to lands and forest resources. In contrast, the Dutch colonial State was gained millions of guldens for economic profit from the expropriation of the native land and from unpaid native slaves who worked in the Dutch plantation sectors. Abstrak: Artikel ini bertujuan untuk menganalisis sejarah perubahan hak milik tanah di kepulauan Indonesia, dan bagaimana hukum tentang agraria dibentuk, khususnya pada zaman penjajahan Belanda. Setelah kolonial Hindia Belanda memproklamirkan berdirinya the Netherland East Indies (NEI) pada abad ke 18, dan menyatakan diri sebagai negara yang berdaulat atas seluruh wilayah Hindia Timur (Indonesia), telah menyebabkan peran hak kolektif atas tanah adat dihapus dengan adanya system hukum Eropa (Hukum Sipil). Penerapan system hukum sipil oleh penjajah Belanda yang menyatakan bahwa tanah-tanah yang tidak mempunyai legalitas (sertifikat), serta wilayah hutan berserta kekayaannya merupakan properti negara dan dikelola oleh institusi negara (State domain). Sebaliknya, bagi masyarakat adat, kekayaan tersebut merupakan milik adat, baik secara individu maupun kelompok. Hal ini telah diakui berdasarkan hukum adat, dimana wilayah (tanah adat) beserta kekayaan di dalamnya merupakan warisan dari leluhurnya. Lebih jauh, pengaruh penerapan system hukum agrarian/sipil Eropa telah menyebabkan dampak negative terhadap kepemilikan tanah adat, dimana hak-hak milik (komunal) mereka menjadi hilang. Sebaliknya, kolonial Belanda memperolah keuntungan ekonomi jutaan gulden dari kegiatan eksploitasi dan kompensasi dari hak konsesi, serta dari perbudakaan rakyat diperusahaan-perusahan perkebunan milik kolonial Belanda. Kata Kunci: Kolonial Belanda, Kebijakan Ekonomi, Tanah Milik Indonesia